Hobbes: a biography - Martinich, Aloysius (Cambridge University Press, 1999)
"Thomas Hobbes (1588-1679) is now recognized as one of the fathers of modern philosophy and political theory. In his own time he was as famous for his work in physics, geometry, and religion. The controversy surrounding his life never abated: the Catholic Church placed his books on the Index, and Oxford University dismissed faculty for being Hobbists." "A. P. Martinich has written the completest and most accessible biography of Hobbes available. The book takes full account of the historical and cultural context in which Hobbes lived, drawing on both published and unpublished sources. It will be a great resource for philosophers, political theorists, and historians of ideas. The style will also ensure that the book appeals to general readers with an interest in the history of philosophy, the rise of modern science, and the English Civil War."--BOOK JACKET